Mitochondrial bioenergetics dysfunction in T2DM: linking oxidative stress to insulin resistance - Feng, Zheng; Tan, Zhenlin; Lu, Donghui (Frontiers in Endocrinology, 2025)
Insulin resistance (IR) is a core pathological feature of type 2 diabetes mellitus (T2DM) and is closely associated with mitochondrial dysfunction in insulin-sensitive tissues, including skeletal muscle, liver, and adipose tissue. Mitochondrial abnormalities—such as impaired oxidative phosphorylation (OXPHOS), dysregulated tricarboxylic acid (TCA) cycle, excessive reactive oxygen species (ROS) production, and altered mitochondrial dynamics—can contribute to IR by oxidatively modifying insulin-signaling proteins and activating inflammatory pathways (JNK/NF-κB). Recent work also implicates microRNAs (miRNAs) as modulators that link mitochondrial function and redox balance to insulin action; however, their magnitude and tissue specificity in human T2DM remain to be defined. Therapeutic strategies that target mitochondrial bioenergetics and redox homeostasis show promise, while miRNA-directed approaches are emerging. This review provides an explanatory synthesis aimed at distinguishing associations within the mitochondria-ROS-insulin resistance axis supported by solid evidence from findings influenced by specific contexts, and outlines translational opportunities and their associated delivery bottlenecks.